2019
DOI: 10.1109/access.2019.2894641
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Data Fusion Based on Optimized Weighted Least-Squares Algorithm for Multi-Target Tracking

Abstract: The outliers remove, the classification of effective measurements, and the weighted optimization method of the corresponding measurement are the main factors that affect the positioning accuracy based on range-based multi-target tracking in wireless sensor networks. In this paper, we develop an improved weighted least-square algorithm based on an enhanced non-naive Bayesian classifier (ENNBC) method. According to the ENNBC method, the outliers in the measurement data are removed effectively, dataset density pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…In this section, the proposed clustering method is compared with the DBSCAN, the k-means [19]- [21], the FCM [22], the PCM [5], the AMPCM [20], [23], and the APCM in a typical scene. Then, the experimental results for the scenes 5: using (27) update the cluster centers θ (l) ; 6: using (26) update the center line segment L (l) of each cluster; 7: using (25) update the Kernel function K (l) ; 8: using (31) update the membership degree matrix U (l) ; 9: for i ← 1 to n do Fig.3(b) show that the proposed clustering method is superior than the other several clustering algorithms.…”
Section: Experiments Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, the proposed clustering method is compared with the DBSCAN, the k-means [19]- [21], the FCM [22], the PCM [5], the AMPCM [20], [23], and the APCM in a typical scene. Then, the experimental results for the scenes 5: using (27) update the cluster centers θ (l) ; 6: using (26) update the center line segment L (l) of each cluster; 7: using (25) update the Kernel function K (l) ; 8: using (31) update the membership degree matrix U (l) ; 9: for i ← 1 to n do Fig.3(b) show that the proposed clustering method is superior than the other several clustering algorithms.…”
Section: Experiments Resultsmentioning
confidence: 99%
“…At the intersection of roads or highways, the radar speedometer is installed to monitor the speed of passing vehicles. However, due to technical limitations, some false detections and missed detections may occur during the speed measurement process, and the intelligent lane separation algorithms can greatly improve this effect [3]- [5]. However, in the application of actual scenes, it is often found that these lane separation algorithms are not accurate in judging the lane of illegal vehicles, which triggers the camera of the wrong lane, resulting in the illegal vehicle capture failure and escape from legal sanctions.…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate the performance of the proposed algorithm for tracking adjacent targets, several simulations have been done and compared with some existing algorithms, namely K-means [16], Fuzzy C-means(FCM) [14] and EKFCM [13] clustering algorithm, which are all combined with the same tracking EKF algorithm. Besides, the root mean square error (RMSE) and Mean RMSE (MMSE) of the position are chosen as performance metrics [25].…”
Section: Simulation Of Tracking Performancementioning
confidence: 99%
“…In general, there are two kinds of state-of-the-art methods dealing with sampling points for respective targets: with or without the probability model [11][12][13][14][15]. While the computational complexity of the former increases as the model becomes more complicated, the latter saves a large number of complex calculations and includes two different methods: clustering and classification algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-target tracking with radar is also a hot issue in intelligent transportation research [4][5][6]. By tracking passing vehicles, risky driving behavior can be predicted and an early warning signal can be issued [7,8]. Vehicle tracking helps to reduce the occurrence of traffic accidents, and also helps the development of intelligent transportation [9].…”
Section: Introductionmentioning
confidence: 99%